1991
DOI: 10.1177/002221949102401005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Transitional Training Program for Young Adults with Learning Disabilities

Abstract: A study was conducted in 1988-1990 at Lesley College's (Cambridge, Massachusetts) Threshold Program, one of the few campus-based, comprehensive transition programs in the country for young adults with learning disabilities functioning in the low-average intellectual range. The goal of the study was to assess the ability of program graduates from the classes of 1984 to 1987 to successfully manage the demands of independent living and competitive employment after intensive training in Threshold's 2- to 3-year pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Research suggests that such self-disclosure could contribute to their employment success, because difficulties due to learning problems tend to arise and need to be addressed on the job (Hoffman et al, 1987;Minskoff, Hawks, Steidle, & Hoffman, 1989). Furthermore, the participants in the ULD course may feel less reluctant to disclose their learning disabilities and more willing to explain the nature of their difficulties in dating relationships than other young adults who find it difficult to disclose their learning disabilities to a social partner, fearing immediate rejection and misinterpretation of the term' 'learning disabilities" as mental retardation (Posthill & Roffman, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that such self-disclosure could contribute to their employment success, because difficulties due to learning problems tend to arise and need to be addressed on the job (Hoffman et al, 1987;Minskoff, Hawks, Steidle, & Hoffman, 1989). Furthermore, the participants in the ULD course may feel less reluctant to disclose their learning disabilities and more willing to explain the nature of their difficulties in dating relationships than other young adults who find it difficult to disclose their learning disabilities to a social partner, fearing immediate rejection and misinterpretation of the term' 'learning disabilities" as mental retardation (Posthill & Roffman, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Selanjutnya, Bransford et al (2000) berpendapat bahwa pembelajaran memberikan pedoman penting untuk penggunaan teknologi dapat mengembangkan kompetensi siswa dan guru yang diperlukan untuk revolusi 4.0. Selain itu, Posthill and Roffman (1991) menyatakan bahwa banyak siswa jarang diberikan penjelasan tentang kesulitan belajar mereka. Allen (1996) berpendapat bahwa 40% kesulitan belajar siswa berhasil sampai ke sekolah menengah tanpa didiagnosis masalah mereka.…”
Section: Pendahuluanunclassified
“…However, previous studies have shown that many students with disabilities not only have a lack of knowledge about their disability but also may not even know they have a disability. One participant in a study by Posthill and Roffman (1991) stated that she "had lived in a world of severe confusion and had never been given an explanation of learning disabilities" (p. 627). This lack of knowledge about one's self leads to the lack of ability to self-advocate.…”
Section: And Findings By Louismentioning
confidence: 99%